Pengaruh Kemampuan Kerja, Kepuasan Kerja, dan Change Management Terhadap Kinerja Pegawai Pada Dinas Persandian dan Statistik Kota Palopo - Nurmalita, Sari; Edi, Maszudi; Duriani, Duriani (ITB AAS Indonesia Surakarta, 2024)
The purpose of this research is to determine the influence of work ability, the influence of job satisfaction, change management on employee performance at the Palopo City Encryption and Statistics Service. This research is a type of quantitative research that is descriptive in nature. Sampling used Nonprobability Sampling with saturated sampling techniques. This research uses a Likert measurement scale. Data processing uses SPSS version 20 software. Work ability has no effect and is not significant on employee performance. Job satisfaction has an influence and is not significant on employee performance. Change Management has a significant and influential effect on employee performance. Work Ability, Job Satisfaction, and Change Management simultaneously (together) and significantly on employee performance. To improve employee performance, it is necessary to increase work ability on employee performance, the higher the job satisfaction, the more it will affect employee performance, Changes in management greatly influence employee performance, every small change, whether increasing or decreasing, will affect a larger increase or decrease in employee performance..